(untitled) (AN-ICON. Studies in Environmental Images [ISSN 2785-7433], 2023)
Water, whether surface or depths, recurrently appears in cinema as a motif and a material. The great symbolic importance this recurrence of the aquatic bears within film leads to calling its different uses into question, especially when it comes to the subaquatic. Addressing the question of the submarine allows going beyond water as a simple surface, and thus to move towards a real habitability of water. Making a history of underwater cinema that includes precinematic devices such as the public aquariums of the late 19th century enables the identification of an aesthetic community, as well as that of a common desire to stage a totalizing perceptive experience of the aquatic element and, in that way, of the image materiality. In line with the various cinematic underwater devices conceived to that end during the 20th century, virtual reality, as a total experience generator, also resorts to the subaquatic as a pretext to immerse the user in the work of art. The recurring fascination for the subaquatic throughout the ages, even more so with the rise of new media, demonstrates how water is a central feature to better define and archeologize the concept of immersion.